THE CAPITAL CITY OF EAST KALIMANTAN: ASSESSING CUSTOMER SERVICE QUALITY AND CUSTOMER SATISFACTION IN ISLAMIC BANKS - Soviati, Dea Kurnia; Tikawati, Tikawati; Yanti, Dharma; Purba, Tanti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The increasing number of Islamic financial institutions in Indonesia has intensified competition, particularly in the aspect of service quality to ensure customer satisfaction. This study aims to analyze the impact of customer service quality on customer satisfaction at a Sharia bank in Samarinda by applying the SERVQUAL dimensions: assurance, reliability, tangibles, empathy, and responsiveness. The research uses a quantitative descriptive method with 98 respondents selected through accidental sampling. Data were analyzed using multiple linear regression with SPSS 21. The results show that reliability, assurance, and empathy significantly influence customer satisfaction, while tangibles and responsiveness do not. Simultaneously, all SERVQUAL dimensions have a significant effect on customer satisfaction. This implies that service quality plays a crucial role in maintaining customer trust and loyalty in Islamic banking.